Electrical Characterization and Modeling of an Innovative Acid/Base Flow Battery - Fabio Ricco Galluzzo; Nicola Campagna; Andrea Culcasi; Alessandro Tamburini; Antonino Oscar Di Tommaso; Giorgio Micale; Rosario Miceli (IEEE Access)
This article presents an experimental validation of modeling approaches for the AB-FB battery, an innovative technology with significant potential for large-scale energy storage applications. The results demonstrate, through experimental analyses that a simplified zero-order equivalent circuit model (ECM) provides adequate accuracy in predicting the electrical behavior of AB-FB cells, particularly in scenarios requiring constant current. In comparison, the more complex electrochemical model, while offering detailed insights into material and electrolyte interactions, is excessively intricate for the sole purpose of describing electrical behavior. Additionally, the study confirms that the discharge characteristics of the AB-FB align with those of established battery technologies, indicating familiarity with its operational principles, mitigating technical risks associated with large-scale deployment. The main contribution is therefore the assessment of the potential use of this technology and the possibility of modeling it with already established approaches.